2017
DOI: 10.15171/jnp.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after ABO-incompatible kidney transplantation; a single-center French study

Abstract: Background: ABO-incompatible (ABOi) is as efficient as ABO-compatible (ABOc) kidneytransplantation in the setting of live-donation. Objectives: To evaluate the long-term outcomes (i.e. >6 months) of 44 consecutive ABOi living-donor kidney-transplants (KTx). The results were compared to those from 44 ABOc KTx that were matched with ABOi-patients on age, gender, and date of transplantation. Patients and Methods: With regards to immunosuppression (IS) only ABOi-patients received pre-transplant IS, that included r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Despite the higher risk of adverse events (pneumonia, urinary tract infections, pyelonephritis, and wound infections) following ABOi LDKT in the early posttransplant period, 35 prior registry-based studies have demonstrated comparable long-term patient survival for ABOi LDKT, 14,[36][37][38][39] and we similarly observed no difference in mortality in A2i versus ABOc recipients. Our research group has previously demonstrated the survival benefit for ABOi LDKT compared with remaining on the waitlist for an eventual ABOc DDKT or LDKT; a similar survival benefit was seen when considering only A2i recipients.…”
Section: Discussionmentioning
confidence: 40%
“…Despite the higher risk of adverse events (pneumonia, urinary tract infections, pyelonephritis, and wound infections) following ABOi LDKT in the early posttransplant period, 35 prior registry-based studies have demonstrated comparable long-term patient survival for ABOi LDKT, 14,[36][37][38][39] and we similarly observed no difference in mortality in A2i versus ABOc recipients. Our research group has previously demonstrated the survival benefit for ABOi LDKT compared with remaining on the waitlist for an eventual ABOc DDKT or LDKT; a similar survival benefit was seen when considering only A2i recipients.…”
Section: Discussionmentioning
confidence: 40%